ANALISIS KINERJA PERBANDINGAN BANK DEVISA BUMN DAN BANK DEVISA SWASTA PADA TAHUN 2006-2011 - Ahmad, Gatot Nazir; Renofa, Naezmi; Mardiyati, Umi (JRMSI - Jurnal Riset Manajemen Sains Indonesia, 2014)
Comparative analysis of performance bank devisa BUMN and bank devisa Swasta. Thesis, Jakarta: Finance Concentration Management, Program Management, Department of Management, Faculty of Economics, University of Jakarta. Researchers aimed to determine the performance bank devisa BUMN and bank devisa Swasta by using the ratio Capital Asset Management (CAR), Return On Asset (ROA), Retrun On Equity (ROE), and Loan to Deposit Ratio (LDR). The samples used were four banks devisa BUMN and four banks devisa Swasta status go public. The data used in this study were obtained from the Annual Banking Financial report. The method of analysis used in this study is a descriptive analysis, test Outliers, and Normality Test Data Test different using paired sample t-test. The results of the analysis using a paired sample t-test between the results obtained bank devisa BUMN and bank devisa Swasta generally have a difference except for Capital Asset Ratio (CAR). The results of this study there was no difference between banks devisa BUMN and bank devisa Swasta. This study also shows that bank devisa Swasta have CAR greater than CAR bank devisa BUMN. keywords: Capital Asset Ratio (CAR), Return On Asset (ROA), Return On Equity (ROE) and Loan to Deposit Ratio (LDR).